Sistem Informasi Berbasis Cloud: Solusi Untuk Bisnis Modern - Dimas Halki Widana; Muhammad Irwan Padli Nasution (Kampus Akademik Publiser, 2025)
Cloud computing is a technology innovation that provides flexible access to computing resources over the internet, enabling operational efficiency, cost reduction, and innovation acceleration for modern businesses. This study uses a qualitative narrative approach to explore the benefits, challenges, and innovation opportunities based on this technology. Findings show that service examples such as SaaS, PaaS, and IaaS support diverse business needs, although challenges such as data security and regulatory compliance must be managed. This technology has proven to be a driver of digital transformation, providing strategic competitiveness, and as a foundation for business sustainability in the digital era.